Overcoming erlotinib resistance with tailored treatment regimen in patient‐derived xenografts from naïve Asian NSCLC patients1. Issue 2 (3rd October 2012) - Yang, Mengmeng; Shan, Baoen; Li, Qiaoxia; Song, Xiaoming; Cai, Jie; Deng, Jianyun; Zhang, Likun; Du, Zhenjian; Lu, Junjie; Chen, Taiping; Wery, Jean‐Pierre; Chen, Yiyou; et al.
Abstract Overall benefits of EGFR‐TKIs are limited because these treatments are largely only for adenocarcinoma (ADC) with EGFR activating mutation. The treatments also usually lead to development of resistances. We have established a panel of patient‐derived xenografts (PDXs) from treatment naïve Asian NSCLC patients, including those containing "classic" EGFR activating mutations. Some of these EGFR‐mutated PDXs do not respond to erlotinib: LU1868 containing L858R/T790M mutations, and LU0858 having L858R mutation as well as c‐MET gene amplification, both squamous cell carcinoma (SCC). Treatment of LU0858 with crizotinib, a small molecule inhibitor for ALK and c‐MET, inhibited tumor growth and c‐MET activity. Combination of erlotinib and crizotinib caused complete response, indicating the activation of both EGFR and c‐MET promote its growth/survival. LU2503 and LU1901, both with wild‐type EGFR and c‐MET gene amplification, showed complete response to crizotinib alone, suggesting that c‐MET gene amplification, not EGFR signaling, is the main oncogenic driver. Interestingly, LU1868 with the EGFR L858R/T790M, but without c‐met amplification, had a complete response to cetuximab. Our data offer novel practical approaches to overcome the two most common resistances to EGFR‐TKIs seen in the clinic using marketed target therapies.